2015
DOI: 10.1016/j.drugalcdep.2015.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of alcohol, marijuana, and inhalant use by American-Indian and white youth living on or near reservations

Abstract: Background Early initiation of drinking, intoxication, marijuana, and inhalant use is associated with negative outcomes and substance use trajectories. Using national datasets, American Indian (AI) youth have been found to initiate substance use earlier than other youth. This study uses a population-based sample of youth living on or near reservations to compare substance use onset for AI and white youth where socioeconomic conditions may be similar for these youth. Methods Student survey data were gathered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 33 publications
2
33
0
Order By: Relevance
“…The studies conducted thus far fairly consistently show ethnic differences in certain SUM templates, but there is an evident lack of investigations that examined the ethnicity-specific prevalence and correlates of SUM in European countries [17,18,19,20]. Also, in European studies authors mostly compared one-specific ethnic group to another heterogeneous group which included several different ethnicities [17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies conducted thus far fairly consistently show ethnic differences in certain SUM templates, but there is an evident lack of investigations that examined the ethnicity-specific prevalence and correlates of SUM in European countries [17,18,19,20]. Also, in European studies authors mostly compared one-specific ethnic group to another heterogeneous group which included several different ethnicities [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a Slovak study compared Roma and non-Roma adolescents, and reported lower prevalence of drunkenness among Roma adolescents [17], while a study from The Netherlands compared Dutch students with their ethnic-minority peers, and found lower prevalence of alcohol drinking among ethnic-minority groups [18]. Additionally, it is generally known the ethnic differences actually extrapolate the differences in socioeconomic status (SES) and scholastic status (i.e., differences in the availability of education, differences in the quality of the education system), which consequently result in different SUM templates between studied ethnicities [17,19,21]. …”
Section: Introductionmentioning
confidence: 99%
“…AI adolescents engage in substance use at higher rates and earlier ages than their non-AI peers (Beauvais, Jumper-Thurman, & Burnside, 2008;Dixon et al, 2007; De Ravello, Everett Jones, Tulloch, Taylor, & Doshi, 2014; Miller, Beauvais, Burnside, & Jumper-Thurman, 2008; Stanley, Harness, Swaim, & Beauvais, 2014; Stanley & Swaim, 2015; Swaim, 2015) and experience more negative consequences of substance use that compromise their social, economic, and physical wellbeing (Indian Health Service, 2013; Keyes et al, 2012; Schinke, Tepavac, & Cole, 2000). Data from the 2007 to 2009 national Youth Risk Behavior Survey (YRBS) indicate that when compared to white adolescents, AI youth are significantly more likely to drink alcohol before age 13 (AI=29.3%; white=19.6%), and to use marijuana (AI=43.9%; white=36.8%), cocaine (AI=9.4%; white=6.8%), and inhalants (AI=18.7%; white=12.8%) in their lifetime (De Ravello et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Heavy use of marijuana is associated with numerous negative outcomes including neurocognitive deficits (Bolla et al, 2002), reduced affective response (Gruber et al, 2009), lowered task performance associated with reduced motivation (Lane et al, 2005), and a variety of psychosocial problems including school dropout, unemployment, and increased risk for delinquency (Fergusson et al, 2008; Green et al, 2010; Lynskey and Hall, 2000). This raises serious public health concerns regarding the substance use trajectories of AI youth, especially considering their early initiation of marijuana use (Stanley and Swaim, 2015; Whitesell et al, 2012). While various risk factors for substance use have been identified for the general population of adolescents (Hawkins et al, 1992), there is evidence that family factors may be especially important in relation to indigenous youth in general (Calabria et al, 2013) and AI youth in particular (LaFromboise et al, 2006; Swaim et al, 1993).…”
Section: Introductionmentioning
confidence: 99%